An Effective Distant Management in Digital Era - Makhamadjanova, Nozima (Researchparks Publishing, 2023)
Over the past decades, the scope of educational management has significantly evolved, influenced by socio-cultural shifts, technological advancements, pedagogical innovations, and global phenomena such as the COVID-19 pandemic. As a result, educational management now demands a wide-ranging set of competencies, including but not limited to leadership skills, change management abilities, digital literacy, and an understanding of diverse learning needs. In the ensuing sections of this paper, we will delve into the intricacies of educational management, discussing its evolution, key principles, challenges, and future directions. We aim to provide a comprehensive overview of the field, shedding light on the integral role it plays in the broader educational landscape.